De novo assembly of a fruit transcriptome set identifies AmMYB10 as a key regulator of anthocyanin biosynthesis in Aronia melanocarpa - Jonathan D. Mahoney; Sining Wang; Liam A. Iorio; Jill L. Wegrzyn; Matthew Dorris; Derek Martin; Bradley W. Bolling; Mark H. Brand; Huanzhong Wang (BMC Plant Biology, 2022)
Abstract Aronia is a group of deciduous fruiting shrubs, of the Rosaceae family, native to eastern North America. Interest in Aronia has increased because of the high levels of dietary antioxidants in Aronia fruits. Using Illumina RNA-seq transcriptome analysis, this study investigates the molecular mechanisms of polyphenol biosynthesis during Aronia fruit development. Six A. melanocarpa (diploid) accessions were collected at four fruit developmental stages. De novo assembly was performed with 341 million clean reads from 24 samples and assembled into 90,008 transcripts with an average length of 801 bp. The transcriptome had 96.1% complete according to Benchmarking Universal Single-Copy Orthologs (BUSCOs). The differentially expressed genes (DEGs) were identified in flavonoid biosynthetic and metabolic processes, pigment biosynthesis, carbohydrate metabolic processes, and polysaccharide metabolic processes based on significant Gene Ontology (GO) biological terms. The expression of ten anthocyanin biosynthetic genes showed significant up-regulation during fruit development according to the transcriptomic data, which was further confirmed using qRT-PCR expression analyses. Additionally, transcription factor genes were identified among the DEGs. Using a transient expression assay, we confirmed that AmMYB10 induces anthocyanin biosynthesis. The de novo transcriptome data provides a valuable resource for the understanding the molecular mechanisms of fruit anthocyanin biosynthesis in Aronia and species of the Rosaceae family.